An overview of the hydrogen value chain in energy transitioning economies: a focus on India - Adiga, Deepak D.; Shenoy, Satish B.; Salunkhe, Pramod B.; Sampath, Suresh (Elsevier, 2025)
India's energy sector is undergoing a major transformation as the nation targets energy independence by 2047 and net-zero emissions by 2070. With a high dependency on energy imports, a strategic shift toward renewable energy and decarbonisation is crucial. Hydrogen has emerged as a promising solution to address energy storage and sustainability challenges, prompting emerging countries to develop strong hydrogen infrastructures. This paper examines various methods involved in the hydrogen value chain, from production to utilisation, from the perspective of transitioning economies. By identifying key parameters and existing gaps, this paper aims to support policymakers and stakeholders in designing effective strategies to accelerate the development of a sustainable and secure hydrogen economy. India currently relies on carbon-intensive hydrogen from fossil fuels. Green hydrogen faces high costs and infrastructure gaps. Despite storage and safety concerns, hydrogen shows strong potential for clean energy and industry transformation.
Keywords: 40 Engineering; 34 Chemical Sciences; 3406 Physical Chemistry; 7 Affordable and Clean Energy; 13 Climate Action; Energy; Hydrogen value chain; Hydrogen economy; Production; Storage; Transportation; Techno-economic assessment